2020
DOI: 10.1055/a-1141-0921
|View full text |Cite
|
Sign up to set email alerts
|

Norway Spruce Balm: Phytochemical Composition and Ability to Enhance Re-epithelialization In Vitro

Abstract: The balm of the Norway spruce (Picea abies) is a well-known traditional herbal medicine used to cure wounds. Even though clinical trials have confirmed its empirical use, the active constituents, their mode of action, and the exact composition of this natural product are still unknown. In this study, the balm was subjected to fractionated extraction and further purified employing flash chromatography, HPLC-PDA-ELSD, preparative and analytical TLC. Hydroxycinnamic acids (1–3), the lignan pinoresinol (4), four h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 13 publications
(36 reference statements)
0
24
0
Order By: Relevance
“…The latter involves resin acids of the abietic- and pimaric-types sharing the same molecular weight of 302 Da and differ only in the position of one double bond and a side chain (compounds 10-1 – 10-7 , Figure 1 ). Hydroxylated resin acids ( 5 – 8 ) and dehydroabietic acid ( 9 ) are easier to separate due to their greater difference in structure and molecular weight [ 13 ]. The obtained fingerprints should facilitate comparison and differentiation of the exudates on a qualitative level.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The latter involves resin acids of the abietic- and pimaric-types sharing the same molecular weight of 302 Da and differ only in the position of one double bond and a side chain (compounds 10-1 – 10-7 , Figure 1 ). Hydroxylated resin acids ( 5 – 8 ) and dehydroabietic acid ( 9 ) are easier to separate due to their greater difference in structure and molecular weight [ 13 ]. The obtained fingerprints should facilitate comparison and differentiation of the exudates on a qualitative level.…”
Section: Resultsmentioning
confidence: 99%
“…Scientific research and literature comparing both the wound-healing properties and the phytochemical composition of the exudates of Picea abies , Pinus nigra , and Larix decidua are relatively scarce. Whereas there are studies about Norway spruce balm [ 13 , 14 , 15 ], data on European larch and black pine are still missing. Norway spruce balm consists of hydroxycinnamic acids such as ferulic acid, lignans such as pinoresinol, and hydroxylated and non-hydroxylated diterpene resin acids as main compounds [ 13 ] (see Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With regard to pinoresinol, the literature on its effects on wound healing is still very limited. A recent study showed that pinoresinol is able to stimulate the proliferation and migration of keratinocytes in culture, enhancing the re-epithelialisation of cell-free zones in a dose-dependent manner with better results at 10 uM concentration [ 78 ]. These results have also been observed in other cell lines, such as fibroblasts.…”
Section: Resultsmentioning
confidence: 99%
“…Exudates of Pinaceae are used in traditional medicine to treat wounds 1 2 . The balms of Picea abies, Larix decidua and Pinus nigra were tested in a HaCaT keratinocyte based in vitro assay for their potential to boost re-epithelialization as measure for wound closure.…”
mentioning
confidence: 99%